Liability of Intermediary Parties in the Context of Copyright Protection: A Case Study of 41pk/Pdt.Sus-Hk/2021 - Satrio, Bagas Putra; Wasitaatmadja, Fokky Fuad; Machmud, Aris (Jurnal Hukum Replik, 2024)
In this study, the researcher aims to examine the practice of re-performing songs, commonly referred to as "song covers," as regulated under Indonesian Law No. 28 of 2014 on Copyright. The research focuses on three main aspects. First, it seeks to identify how copyright regulations are applied in the context of reusing copyrighted works, specifically in the form of songs, in accordance with the copyright law. Second, it analyzes the legal consequences imposed on copyright violators in this context. Third, it evaluates the compatibility of the Supreme Court Decision No. 41PK/Pdt.Sus-HK/2021 with the principles of Legal Protection Theory. This study employs a Normative Juridical approach, based on the principles of norms and laws applicable in Indonesia. The researcher uses this approach to refer to the legal norms and regulations in effect in the country. The research draws on legal materials from literature as both primary and secondary sources. Based on the analysis, the researcher concludes that anyone intending to upload song covers on social media platforms such as YouTube must comply with the economic rights held by the performers. This includes steps like obtaining permissions or licenses and paying royalties for the copyrighted works.Keywords: Song Covers; Copyright; Exclusive Rights; Intellectual Works; License; Royalties